Investigating the Impact of Financial Literacy and Income on Financial Behaviors Among Millennials - Remund Kefela Hilgert; Masruki Luttrell (Institute of Accounting Research and Novation (IARN), 2023)
This study delves into the intricate relationships between financial literacy, income levels, and financial management behaviors among the millennial generation. The research aims to analyze how these variables interplay and influence the financial decision-making of this dynamic cohort. Drawing on a cross-sectional research design, data was collected through surveys and assessments from a diverse sample of millennials aged between 25 and 40. The study measured financial literacy through standardized questionnaires, evaluated income levels, and assessed financial management behaviors including savings rates, investment choices, and debt management indicators. The findings highlight a robust correlation between higher financial literacy and more responsible financial behaviors among millennials. Individuals with a better understanding of financial concepts showcased prudent financial practices, indicating the significance of financial literacy in shaping financial decision-making. Income levels demonstrated a substantial impact on financial behaviors, underscoring financial flexibility and opportunities higher incomes afford. Even among higher income earners, individuals with low financial literacy exhibited suboptimal financial decisions, indicating that financial literacy plays a pivotal role in shaping financial behaviors, often outweighing the impact of income levels alone. The study's implications emphasize the urgent need for comprehensive financial education initiatives tailored to the needs of millennials. By equipping individuals with financial knowledge and skills, regardless of their income levels, these findings suggest a pathway towards more informed financial decision-making, fostering long-term financial well-being within this demographic. These insights offer a foundation for policymakers, financial institutions, educators, and individuals themselves to invest in and promote financial literacy programs, thus nurturing a financially savvy and resilient millennial generation.